2015
DOI: 10.1074/jbc.m115.639732
|View full text |Cite
|
Sign up to set email alerts
|

Tag7 (PGLYRP1) in Complex with Hsp70 Induces Alternative Cytotoxic Processes in Tumor Cells via TNFR1 Receptor

Abstract: Background:A complex containing an innate immunity protein Tag7, and Hsp70 kills various cancer cells. Results: Tag7 and its complex with Hsp70 bind to the TNFR1 receptor, but only the Tag7-Hsp70 complex induces a cytotoxic effect via apoptosis and necroptosis. Conclusion: A new ligand has been found for the TNFR1 death receptor. Significance: Tag7 may be used as an inhibitor of the TNF-␣-induced cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 33 publications
(42 reference statements)
3
42
0
4
Order By: Relevance
“…The cytotoxicity of the medium conditioned by CD8+ lymphocytes on L929 cells was also completely suppressed by anti‐Tag7 and anti‐Hsp70 antibodies, suggesting the dependence of cytotoxic effect on the presence of Tag7–Hsp70 complex in the medium. In view of our data that this complex induces cell death pathways by interacting with the TNFR1 receptor , we performed experiments with anti‐TNFR1 antibodies and found that they also inhibited the cytotoxic effect on L929 cells, confirming that the medium conditioned by CD8+ lymphocytes contained the Tag7–Hsp70 complex (Fig. B).…”
Section: Resultssupporting
confidence: 52%
“…The cytotoxicity of the medium conditioned by CD8+ lymphocytes on L929 cells was also completely suppressed by anti‐Tag7 and anti‐Hsp70 antibodies, suggesting the dependence of cytotoxic effect on the presence of Tag7–Hsp70 complex in the medium. In view of our data that this complex induces cell death pathways by interacting with the TNFR1 receptor , we performed experiments with anti‐TNFR1 antibodies and found that they also inhibited the cytotoxic effect on L929 cells, confirming that the medium conditioned by CD8+ lymphocytes contained the Tag7–Hsp70 complex (Fig. B).…”
Section: Resultssupporting
confidence: 52%
“…The Fas receptor belongs to the family of cell death receptors that have been shown to switch between alternative signaling processes. In our experiments on the cytotoxic effect of the Tag7-Hsp70 complex, which is a ligand for the TNF-R1 receptor, the blocking of apoptosis with inhibitors of caspases 3 and 8 resulted in activation of the RIP1dependent necroptosis [Yashin et al, 2015]. In this study, the number of cells dying by way of necroptosis (after 20-h incubation with lymphocytes) has not increased after the inhibition of apoptosis (cell death after 3 h).…”
Section: Discussionmentioning
confidence: 53%
“…Another promising strategy for reduction of inflammation in the autoimmune diseases is to develop agents preventing signal transduction through the TNF-TNFR1 system [14]. For example, we have recently demonstrated that innate immunity regulator Tag7 can bind to the TNFR1 protein, a specific TNF receptor [15].…”
Section: Introductionmentioning
confidence: 99%